Promotional Strategy For Graduation Photography Services Through Instagram Social Media @Univisual_ - Gilang Merdeka; Moch Rizky Alhamdany; Farida Nurfalah; Welly Wihayati (Journal of Social Science, 2025)
The use of the Instagram platform as a promotional medium has developed into one of the most efficient marketing tactics during the development of the digital era like now. Instagram is not only a platform to share image- or video-based content, but also serves to build relationships with consumers. The increase was due to attractive promotions and consumer satisfaction with the services provided by Univisual. Therefore, this study aims to find out what promotional strategies, Instagram content, and features are used by Univisual to attract consumer interest. This research uses Promotion Mix Theory, namely Advertising, and Sales Promotion. The method carried out in this study is qualitative. Data collection techniques include observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and conclusion drawn. The subjects in this study consisted of three informants, namely owners, admins, and potential consumers. The results of this study show that the Promotion Mix strategy implemented by Univisial has proven to be effective in increasing consumer interest in the services provided. Univisual takes full advantage of the features on Instagram as a promotional medium, sharing content, and utilizing Instagram ads. This is shown by the responses given by the informants regarding the promotional strategy carried out by Univisual.